Early steroid pulse therapy for children with suspected acute encephalopathy: An observational study. Issue 30 (30th July 2021) - Ishida, Yusuke; Nishiyama, Masahiro; Yamaguchi, Hiroshi; Tomioka, Kazumi; Takeda, Hiroki; Tokumoto, Shoichi; Toyoshima, Daisaku; Maruyama, Azusa; Seino, Yusuke; Aoki, Kazunori; Nozu, Kandai; Kurosawa, Hiroshi; et al.
Abstract : Abstract: Steroid pulse therapy is widely used to treat virus-associated acute encephalopathy, especially the cytokine storm type; however, its effectiveness remains unknown. We sought to investigate the effectiveness of early steroid pulse therapy for suspected acute encephalopathy in the presence of elevated aspartate aminotransferase (AST) levels. We enrolled children admitted to Hyogo Children's Hospital between 2003 and 2017 with convulsions or impaired consciousness accompanied by fever (temperature >38°C). The inclusion criteria were: refractory status epilepticus or prolonged neurological abnormality or hemiplegia at 6 hours from onset, and AST elevation >90 IU/L within 6 hours of onset. We excluded patients with a neurological history. We compared the prognosis between the groups with or without steroid pulse therapy within 24 hours. A good prognosis was defined as a Pediatric Cerebral Performance Category Scale (PCPC) score of 1-2 at the last evaluation, within 30 months of onset. Moreover, we analyzed the relationship between prognosis and time from onset to steroid pulse therapy. Fifteen patients with acute encephalopathy and 5 patients with febrile seizures were included in this study. Thirteen patients received steroid pulse therapy within 24 hours. There was no between-group difference in the proportion with a good prognosis. There was no significant correlation between PCPC and timing of steroid pulse therapy (rs = 0.253, P  = .405). Even after excluding 2 patients with brainstem lesions, no significant correlation between PCPC and steroid pulse therapy timing (rs = 0.583, P  = .060) was noted. However, the prognosis tended to be better in patients who received steroid pulse therapy earlier. Steroid pulse therapy within 24 hours did not improve the prognosis in children with suspected acute encephalopathy associated with elevated AST. Still, even earlier administration of treatment could prevent the possible neurological sequelae of this condition.